Economic Evaluation of Citrus Greening Management and Control Strategies - Allen Morris; Ron Muraro (EDIS)
FE712, a 7-page illustrated article by Allen Morris and Ron Muraro, explores the profitability of various types of control measures now being practiced in the citrus industry. Published by the UF Department of Food and Resource Economics, June 2008.